Molecular Insights Into O-Linked Glycan Utilization by Gut Microbes - González-Morelo, Kevin J.; Vega-Sagardía, Marco; Garrido, Daniel (Frontiers in Microbiology, 2020)
O-linked glycosylation is a post-translational modification mainly found in eukaryotic cells, which covalently attaches oligosaccharides to secreted proteins in certain threonine or serine residues. Most of O-glycans have N-acetylgalactosamine as a common core. Several glycoproteins such as mucins, immunoglobulins and caseins are examples of O-glycosylated structures. These glycans are further elongated with other monosaccharides and sulfate groups. Some of them could be found in dairy foods, while others are produced endogenously, in both cases interacting with the gut microbiota. Interestingly, certain gut microbes can access, release, and consume O-linked glycans as a carbon source. Among these, Akkermansia muciniphila, Bifidobacterium bifidum and Bacteroides thetaiotaomicron are prominent O-linked glycan utilizers. Their consumption strategies include specialized α-fucosidases and α-sialidases, in addition to endo-α-N-acetylgalactosaminidases that release galacto-N-biose from peptides backbones. O-linked glycan utilization by certain gut microbes represents an important niche that allows them to predominate and modulate host responses such as inflammation. Here we focus on the distinct molecular mechanisms of consumption of O-linked N-acetylgalactosamine glycans by prominent gut microbes, especially from mucin and casein glycomacropeptide, highlighting the potential of these structures as emerging prebiotics.